Assessment and optimisation of low-GWP refrigerants during two-phase heat transfer inside small-diameter smooth tubes. (September 2020) - Longo, Giovanni A.; Mancin, Simone; Righetti, Giulia; Zilio, Claudio; Brown, J. Steven
Highlights: This paper presents an assessment of new low-GWP refrigerants. The assessment couples experimental measurements and theoretical analysis. The theoretical analysis is based on the total temperature penalisation (TTP) criteria. The TTP analysis was also used for process optimisation. Abstract: This paper presents an assessment of new low-GWP refrigerants through coupling the experimental measurement of thermal and hydraulic performances to a theoretical evaluation based on the Total Temperature Penalisation (TTP) criterion for the specific case study of two-phase heat transfer inside a small-diameter smooth tube. The TTP analysis was also used for process optimisation. The TTP analysis identifies R32 and two hydrocarbon refrigerants R290 and R1270 as the most suitable low-GWP substitutes for R410A and R404A, respectively. R152a, R1234yf and R1234ze(E) are appropriate low-GWP alternatives for R134a, while R1234ze(Z) and R1233zd(E) emerge as appropriate low-GWP, near drop-in substitutes for R245fa. HydroFluoroCarbon (HFC) and HydroFluoroOlefin (HFO) refrigerants possess values of the optimum mass velocity in two-phase heat transfer inside small-diameter smooth tubes nearly double that of HydroCarbon (HC) refrigerants, and the optimum mass velocities for in-tube condensation are generally much higher than those in flow boiling.